Rational Design and Synthesis of Selective PRMT4 Inhibitors: A New Chemotype for Development of Cancer Therapeutics. (4th March 2021) - Sutherland, Mathew; Li, Alice; Kaghad, Anissa; Panagopoulos, Dimitrios; Li, Fengling; Szewczyk, Magdalena; Smil, David; Scholten, Cora; Bouché, Léa; Stellfeld, Timo; Arrowsmith, Cheryl H.; Barsyte, Dalia; et al.
Abstract: Protein arginine N ‐methyl transferase 4 (PRMT4) asymmetrically dimethylates the arginine residues of histone H3 and nonhistone proteins. The overexpression of PRMT4 in several cancers has stimulated interest in the discovery of inhibitors as biological tools and, potentially, therapeutics. Although several PRMT4 inhibitors have been reported, most display poor selectivity against other members of the PRMT family of methyl transferases. Herein, we report the structure‐based design of a new class of alanine‐containing 3‐arylindoles as potent and selective PRMT4 inhibitors, and describe key structure–activity relationships for this class of compounds. Abstract : Arylindole alanine‐based inhibitors : A new class of potent and selective PRMT4 inhibitors has been identified. We studied the structure–activity relationships and arrived at a rationale for the observed selectivity by using the co‐crystal structure of our compound with PRMT6 and comparing it with reported PRMT4 co‐crystal structures.